INTERCULTURAL DIMENSION IN ENGLISH LANGUAGE TEACHING FROM AN INTERDISCIPLINARY PERSPECTIVE: AN EXPERIENCE REPORT IN BRAZILIAN PUBLIC HIGH SCHOOL - Huguenin Corrêa, Tamires (Revista Gênero e Interdisciplinaridade, 2026)
This article presents an experience report on integrating the intercultural dimension into English language teaching in Brazilian public high schools, based on practices at CEFET-RJ, Valença campus, with a focus on interdisciplinarity and citizenship education. Based on Morin (2000), Byram (2008), and the National Common Curricular Base (BRASIL, 2018), the study emphasizes the need to move beyond traditional grammar-centered instruction by incorporating cultural and critical approaches that promote respect for diversity and global competencies. Using a qualitative methodology, a questionnaire was shared with second-year students at the Integrated Technical High School program, revealing that both classes and the Nations Fair project serve as important contexts for fostering intercultural understanding, creativity, and teamwork. The findings suggest that embedding the intercultural dimension in English teaching is crucial for enhancing student agency and addressing the demands of holistic education in Brazilian public schools.